Polymeric Coatings for Skutterudite-Based Thermoelectric Materials - Witold Brostow; IKang Chen; Haley E. Hagg Lobland (Lubricants, 2022)
Thermoelectric (TE) devices have short service lives. These materials undergo thermal degradation at elevated temperatures by processes such as oxidation or sublimation. Our substrates were skutterudite-based TE materials. We covered their surfaces with a liquid high-temperature polymer (HTP)—crosslinked after the deposition, what converted those surfaces into solid coatings. Sintering was performed at 250 °C for times of up to 48 h on both uncoated (control) and HTP-coated samples. The changes caused by thermal degradation were evaluated by thermogravimetric analysis, electrical resistivity, and energy-dispersive X-ray spectroscopy, and observed by scanning electron microscopy. Significant mitigation of oxidation and sublimation of our TE materials was achieved.